(3eHGOFg hCSGSjGJgs - (3RjO efjQ(B, (3YHhjs ((3YeGf(B;(3YeGf(B:s (3OGQ CSGeI ddfTQ hGdJhRjY(B;(3OGQ GdeTQb GdKbGaj(B,s, 2006)
(3jVe GdeONd Edi GdJfXje hGdCSGdjH, fXQjGJ GdJfXje, GdefXeI, GdEOGQI HGdCgOGa, GdHjFI GdJfXjejI, GdefGN GdJfXjej, GdELQGAGJ hJHSjWgG hGdCOdI GdEOGQjI, bjGS GdYed GdYed hJbjje GdCOGA GdeDSSj, GdJWhjQ hGdJZjQ GdJfXjej, GdgfOQIs
(3HjHdjhZQGajG(B: (3U U(B.239s
Keywords: (3EOGQI GdCYeGds; (3GdEOGQI GdYGeIs; (3GdJfXjes